Sorting and the Output Loss due to Search Frictions - Pieter A. Gautier; Coen N. Teulings (Tinbergen Institute, 2011)
We analyze a general search model with on-the-job search and sorting of heterogeneous workers into heterogeneous jobs. This model yields a simple relationshipbetween (i) the unemployment rate, (ii) the value of non-market time, and (iii) themax-mean wage differential. The latter measure of wage dispersion is more robustthan measures based on the reservation wage, due to the long left tail of the wagedistribution. We estimate this wage differential using data on match quality andallow for measurement error. The estimated wage dispersion and mismatch for theUS is consistent with an unemployment rate of 5%. Finally, we find that withoutsearch frictions, output would be 6.6% higher.
Keywords: E24; J62; J63; J64; 330; Sorting; search frictions; wage dispersion; unemployment; mismatch; on-the-job search; output loss; business stealing; Suchtheorie; Arbeitslosigkeit; Lohnstruktur; Schätzung; USA